Effects of non-invasive brain stimulation on balance control in patients with multiple sclerosis: a systematic review and meta-analysis - Zhang, Longtao; Sun, Yanxiao; Diao, Zhihao; Jiang, Yifan; Hu, Yufei; Ma, Yuxia (Frontiers in Neurology, 2025)
ObjectiveThis study aims to evaluate the effects of non-invasive brain stimulation (NIBS) on balance control in patients with multiple sclerosis (MS) through a systematic review and meta-analysis. The goal is to identify the most effective treatment strategies and provide valuable evidence for clinical decision-making.MethodsPubMed, Web of Science, Embase, Scopus, Cochrane Library, ClinicalTrials.gov and CNKI Scholar were searched for randomized controlled trials (RCTs) on the effects of NIBS on balance control in patients with MS. The search period was from the inception of each database to August 11, 2025. The Timed Up and Go test (TUG) and the Berg Balance Scale (BBS) are the primary outcome measures, with adverse events being the secondary outcome measure. Two researchers independently performed literature screening, data extraction and quality assessment. The quality of the included trials was assessed using the Cochrane Risk of Bias tool (RoB 2.0) and the GRADE proGDT software was used to evaluate the evidence grading recommendation standards (GRADE) for outcomes. Data were analyzed using RevMan 5.4 and StataMP 18 software. For binary variables, the effect size is measured using the risk ratio (RR), while for continuous variables, the effect size is measured using the mean difference (MD), with a 95% confidence interval (CI). Heterogeneity was explored through subgroup analysis, meta-regression, and sensitivity analysis to assess the robustness of the results. A funnel plot was constructed, and Egger’s test was performed to evaluate potential publication bias.ResultsA total of 17 RCTs with 514 patients were included. Meta-analysis showed that NIBS can shorten the time taken for TUG [MD = −1.03, 95% CI (−1.86, −0.20)] and improve BBS scores [MD = 3.35, 95% CI (1.31, 5.39)], indicating that NIBS may improve both dynamic and static balance. Subgroup analysis revealed that interventions lasting ≥4 weeks were associated with a reduction in TUG completion time and an increase in BBS scores. Furthermore, transcranial direct current stimulation (tDCS) demonstrated favorable effects on both TUG and BBS outcomes, while evidence supporting the efficacy of repetitive transcranial magnetic stimulation (rTMS) remained limited. Although adverse events such as itching, warmth, tension, and fatigue were reported in NIBS group, these were generally mild and transient.ConclusionThis study suggests that NIBS may serve as an effective adjunctive therapy for balance rehabilitation in patients with MS, showing benefits in both dynamic and static balance. However, its application is accompanied by mild and transient adverse effects, necessitating a careful balance between efficacy and safety in clinical practice. The current evidence is limited by heterogeneity among included studies and short follow-up durations. Future research should focus on large-scale, high-quality RCTs to further validate the long-term efficacy of NIBS, optimize stimulation parameters, and promote the development of individualized treatment strategies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier: CRD420251121717.